A soft biomolecule actuator based on a highly functionalized bacterial cellulose nano-fiber network with carboxylic acid groups. Issue 1 (7th October 2015) - Wang, Fan; Jeon, Jin-Han; Park, Sukho; Kee, Chang-Doo; Kim, Seong-Jun; Oh, Il-Kwon
Abstract : A soft biomolecular electro-mechanical actuator showing high actuation performance was fabricated based on functionalized bacterial cellulose with carboxylic acid groups. Abstract : Upcoming human-related applications such as soft wearable electronics, flexible haptic systems, and active bio-medical devices will require bio-friendly actuating materials. Here, we report a soft biomolecule actuator based on carboxylated bacterial cellulose (CBC), ionic liquid (IL), and poly (3, 4-ethylenedioxythiophene)–poly(styrenesulfonate) (PEDOT:PSS) electrodes. Soft and biocompatible polymer–IL composites were prepared via doping of CBC with ILs. The highly conductive PEDOT:PSS layers were deposited on both sides of the CBC–IL membranes by a dip-coating technique to yield a sandwiched actuator system. Ionic conductivity and ionic exchange capacity of the CBC membrane can be increased up to 22.8 times and 1.5 times compared with pristine bacterial cellulose (BC), respectively, resulting in 8 times large bending deformation than the pure BC actuators with metallic electrodes in an open air environment. The developed CBC–IL actuators show significant progress in the development of biocompatible and soft actuating materials with quick response, low operating voltage and comparatively large bending deformation.